Proceedings of the 2nd International Workshop on Multimedia for Personal Health and Health Care 2017
DOI: 10.1145/3132635.3132636
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Benefits of CCA and SVMs for SSVEP-based BCIs in Real-world Conditions

Abstract: In this paper we propose a novel method for SSVEP classification that combines the benefits of the inherently multi-channel CCA, the state-of-the-art method for detecting SSVEPs, with the robust SVMs, one of the most popular machine learning algorithms. The employment of SVMs, except for the benefit of robustness, provides us also with a confidence score allowing to dynamically trade-off the trial length with the accuracy of the classifier, and vice versa. By balancing this trade-off we are able to offer perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For subject-1, the improvement in classification accuracy is evaluated as 27.67% against LASSO method and 7.81% against CNN method. Similarly, for subject S-6, the enhancement in classification accuracy is observed as 12.32% and 41.98% whereas the enhancement in classification accuracy considering subject S- Classification accuracy SVM, LDA, K-NN, [22] 79.47%, 64.11%, 49.40% K-NN, C4.5, CNN [23] 46.17%, 49.41%, 69.03% SVM along with CCA [24] 93.11% CNN [25] 73.74% SVM [26] 88.3% CNN+LOSO [27] 69.75% CNN [27] 80.83% Proposed AFCA Model 93.48%…”
Section: Comparative Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…For subject-1, the improvement in classification accuracy is evaluated as 27.67% against LASSO method and 7.81% against CNN method. Similarly, for subject S-6, the enhancement in classification accuracy is observed as 12.32% and 41.98% whereas the enhancement in classification accuracy considering subject S- Classification accuracy SVM, LDA, K-NN, [22] 79.47%, 64.11%, 49.40% K-NN, C4.5, CNN [23] 46.17%, 49.41%, 69.03% SVM along with CCA [24] 93.11% CNN [25] 73.74% SVM [26] 88.3% CNN+LOSO [27] 69.75% CNN [27] 80.83% Proposed AFCA Model 93.48%…”
Section: Comparative Analysismentioning
confidence: 86%
“…The obtained classification accuracy is mean of varied data lengths (0.2-0.6). The improvement of classification accuracy using proposed AFCA model against [24] is 0.38% and against [25] is 26.75%, against [26] is 5.85% and against [27] is 15.63%. Thus, proposed AFCA model outperforms all the SSVEP algorithms in terms of classification accuracy.…”
Section: Comparative Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The experimental results demonstrated that the architecture could be used for classification of an SSVEP‐BCI system and real‐time application of BCI. In 2017, Chatzilari et al [75] proposed a brain electrolytic‐code algorithm that combined the multichannel CCA decoding and SVM algorithms. The SVM algorithm provided a confidence score, which allowed dynamic adjustment of the length of analysis data and accuracy of the classifier.…”
Section: Decoding Algorithm For Ssvepmentioning
confidence: 99%